(untitled) (International Journal of Engineering and Computer Science, 2018)
The human immunodeficiency virus (HIV) epidemic continues to be associated with misconceptions and misinformed opinions, which increase the risk of HIV transmission. Therefore, the present study aimed to identify the determinant factors among different socioeconomic and demographic factors affecting misconceptions about HIV transmission among married men in Bangladesh. Data and necessary information of 2778 married men were extracted from the Bangladesh Demographic and Health Survey 2011. Three types of misconceptions were considered. Both bivariate and multivariate analyses were used as the statistical tools to determine the factors affecting misconceptions about HIV transmission. The results revealed that misconceptions are more prevalent among men who are older, less educated, live in rural areas and have poor economic conditions. The respondent’s age, region, residence, education, wealth index, and occupation are significantly associated with the misconceptions. Finally, logistic regression analysis identified age, region, place of residence, education, wealth index, and occupation media as significant predictors. Intervention programs should be aimed at HIV prevention via education and awareness programs to reduce misconceptions as important parts of the prevention strategy.